The Effectiveness of Jigsaw Type Assisted with Card Problems on Learning Outcomes and Responsibilities of Cell Material - Pangestika, Nandita; Setiati, Ning (Journal of Biology Education, 2019)
The research aims to analyse the effectiveness of the implementation of cooperative learning of jigsaw-type with the card problem on learning outcomes and responsibilities of student cell material in high school. This is done because students ' understanding of the cell material is still lacking, about 60% of students have not reached the KKM. This research was conducted at the Sint Louis High School in Semarang at the time of school year 2019/2020. The samples in this study were all learners with saturated sampling techniques. The design of this research is One Group Pretest-Posttest Design. The results show the value of N-gain students in medium and high categories, the average character score of student responsibilities reaches good and very good category, so that cooperative learning of Jigsaw type assisted with card problem for effective learning outcomes and student responsibility character.